2017
DOI: 10.1177/0361684317720187
|View full text |Cite
|
Sign up to set email alerts
|

Unacknowledged Rape and Re-Victimization Risk

Abstract: The majority of college women who experience rape do not conceptualize their experience as a victimization, that is, they are unacknowledged victims. There is some initial evidence that unacknowledged victims are at elevated re-victimization risk relative to acknowledged victims. In the current study, we sought to identify mediators of the association between acknowledgment of rape and re-victimization in a sample of 319 college rape victims; 187 (58.6%) participants completed a 2-month follow-up study. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 61 publications
4
30
1
5
Order By: Relevance
“…This questionnaire was initially developed by Koss (1985) and then modified by Layman and colleagues (1996); it was later expanded by Littleton and colleagues (2006). Responses to these items were coded using the categories developed in later work (Littleton et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This questionnaire was initially developed by Koss (1985) and then modified by Layman and colleagues (1996); it was later expanded by Littleton and colleagues (2006). Responses to these items were coded using the categories developed in later work (Littleton et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Further, resistance behaviors are both a response to the perpetrator’s tactics, as well as likely influence perpetration strategies (e.g., threats of harm, intimidation, physical force) used by the perpetrator (e.g., Balemba & Beauregard, 2012). In addition, given the frequency of pre-assault alcohol and other substance use by the perpetrator and survivor among college women who experienced sexual assaults prior to or during college, and the frequency with which college women who are survivors of sexual assaults are impaired or incapacitated by substances, we included multiple substance-related variables in the LCA (e.g., Krebs et al, 2009; Littleton, Grills-Taquechel, & Axsom, 2009; Littleton et al, 2017). Specifically, we included whether the survivor and perpetrator engaged in binge or non-binge drinking, the level of substance-related impairment experienced by the survivor, and whether the survivor and perpetrator used other drugs prior to the assault.…”
mentioning
confidence: 99%
“…Unfortunately, many young women who suffered gender violence are unacknowledged victims who do not view their experience as a form of victimization (Littleton et al, 2017). Any phenomenon with a gendered view implies observing what is invisible (Salvai, 2013) and requires questioning mental patterns such as TGBs that may have been established and naturalized over centuries (Wolfe and Naimark, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified barriers and factors that impede acknowledgment of SV by victimized women. Littleton et al (2017) found that a closer relationship with the assailant strongly influenced the failure to acknowledge sexual aggression. For example, when the perpetrator was a romantic partner, there was much less acknowledgment of sexual aggression compared with casual or non-romantic partners.…”
Section: Acknowledgment Of Sv and Rc Violence Victimization: Issues And Challengesmentioning
confidence: 99%